Readiness of halal food company to participate in halal food e-marketplace / Azfar Ramli - Ramli, Azfar (2005)
The growth of halal food company in Malaysia nowadays makes Malaysia as a strong potential to be a halal food centre in the world. In order to achieve that, much effort has been done by the government; one of it is by developing an e-marketplace such as ^ribazaar.com and OICtrade.com with the co-operation with OIC and MIMOS. Since there is only one food company that participates in OIC trade e-marketplace, it is essential to know the readiness of halal food company to participate in e-marketplace. The objective of this research is to identify the readiness level of halal food company to participate in halal e-marketplace and also to identify the factors that contributes to the readiness of the halal food company to participate in halal e-marketplace. The data samples was halal processed food company that been classified by MATRADE as a product that have potential to be exported. The primary data was gather from the interview session and as for secondary data, it was gather from journals, books, newspaper, articles and also through internet. There are 28 companies that were selected, but only 16 are willing to co-operate in this research. The data collected were analyzed using SPSS. As a result, the readiness of halal food company to participate in halal emarketplace is medium. Technology is the factor that contribute to the readiness to participate in e-marketplaces whereas, environmental and organizational readiness not the factor for the companies to participate in e-marketplace. For the conclusion, the halal food company should gain more knowledge about e-marketplace and change their perspective of doing business through the web.